The Influence of Accommodation on Retinal Peripheral Refraction Changes in Different Measurement Areas - Weicong Lu; Zisu Peng; Wenzhi Ding; Rongyuan Ji; Yuyin Tian; Chenpei Zhao; Lin Leng (Journal of Ophthalmology)
Background. The change in refraction caused by accommodation inevitably affects the peripheral defocus state and thus may influence the effect of retinal peripheral myopic defocus measures in myopia control. This study investigated accommodation changes in different peripheral retinas under cycloplegia to help improve myopia control. Methods. Fifty-six eyes of fifty-six myopic subjects were recruited for this prospective study. The center and peripheral retina refractions were measured using multispectral refractive topography. The subjects were divided into low-to-moderate myopia group (range: −1.25 D to −6.00 D) and high myopia group (range: −6.25 D to −9.75 D) according to spherical equivalent (SE). The compound tropicamide (0.5% tropicamide and 0.5% phenylephrine) was used to relax the accommodation. The difference between cycloplegia and non-cycloplegia peripheral retinal refraction was analyzed using the t-test. The correlation between eccentricity and changes in peripheral refraction was analyzed using Pearson’s correlation analysis. Results. The manifest refraction of the retina significantly decreased with an increase in eccentricity after cycloplegia. The annular refraction difference value at 50°–53° (ARDV 50–53) showed the largest refraction decrease of 1.31 D compared with the central retinal refraction decrease of 0.84 D. The inferior quadrantal refraction difference value had the least change compared to the other quadrants. The relative peripheral refraction (RPR) changes in refraction difference value (RDV) at 15° (RDV-15), RDV-30, and RDV-45 were less than 0.15 D. When the range of annulus narrowed to 5°, the narrower annulus showed faster change with eccentricity increase in ARDV 30–35, ARDV 35–40, ARDV 40–45, ARDV 45–50, and ARDV 50–53. The RPR was highly correlated with eccentricity (R = 0.938 and P<0.001). The high myopia group had a greater hyperopic shift in the periphery than the low-to-moderate group after cycloplegia. Conclusions. Peripheral refraction showed a significant hyperopic shift after cycloplegia with an increase in eccentricity. The RPR became more hyperopic than the central refraction. The high myopia group showed more hyperopic shifts in the peripheral region. Accommodation should be taken into consideration in peripheral defocus treatment.